Individualized positive end-expiratory pressure setting in patients with severe acute respiratory distress syndrome supported with veno-venous extracorporeal membrane oxygenation. (May 2021) - Yin, Chengfen; Gao, Xinjing; Cao, Chao; Xu, Lei; Lu, Xing
Background: Patients with acute respiratory distress syndrome supported with veno-venous extracorporeal membrane oxygenation benefit from higher positive end-expiratory pressure combined with conventional ventilation during the early extracorporeal membrane oxygenation period. The role of incremental positive end-expiratory pressure titration in patients with severe acute respiratory distress syndrome supported with veno-venous extracorporeal membrane oxygenation remains unclear. This study aimed to determine the preferred method for setting positive end-expiratory pressure in patients with severe acute respiratory distress syndrome on veno-venous extracorporeal membrane oxygenation support. Methods: We retrospectively reviewed all subjects supported with veno-venous extracorporeal membrane oxygenation for severe acute respiratory distress syndrome from 2009 to 2019 in the intensive care units in Tianjin Third Central Hospital. Subjects were divided into two groups according to the positive end-expiratory pressure titration method used: P-V curve (quasi-static pressure-volume curve-guided positive end-expiratory pressure setting) group or Crs (respiratory system compliance-guided positive end-expiratory pressure setting) group. Results: Forty-three subjects were included in the clinical outcome analysis: 20 in the P-V curve group and 23 in the Crs group. Initial positive end-expiratory pressure levels during veno-venous extracorporeal membrane oxygenation were similar in both groups. Incidence rates of barotrauma and hemodynamic events were significantly lower in the Crs group (all p < 0.05). Mechanical ventilation duration, intensive care unit length of stay, and hospital length of stay were significantly shorter in the Crs group than the P-V curve group (all p < 0.05). Subjects in the Crs group showed non-significant improvements in the duration of extracorporeal membrane oxygenation support and 28-day mortality (p > 0.05). Conclusion: Respiratory system compliance-guided positive end-expiratory pressure setting may lead to more optimal clinical outcomes for patients with severe acute respiratory distress syndrome supported by veno-venous extracorporeal membrane oxygenation. Moreover, the operation is simple, safe, and convenient in clinical practice.